From the History of Studies on Old Believers in Northwestern Belarus: Literature Review (Second Half of the 18th Century–1980) - Auseichyk, Uladzimir (Slavistica Vilnensis, 2022)
The article examines the historiography and the current state of research on the Old Believers in Northwestern Belarus. Four basic stages are distinguished in the history of studies on Old Believers in the region: second half of the 18th century – beginning of the 20th century; the interwar period (1920–1930 years); the Soviet period (1950–1980 years); the modern period (1990–2000 years). The characteristic of these stages is given, the methodology of conducted research is analyzed, the value of published works in this direction is revealed. The article analyzes research conducted from the second half of the 18th century to the last two decades of the 20th century. The main attention is given to the analysis of the works published during the second half of the of 19th century and the early 20th century.